2023
DOI: 10.1021/jacs.2c11390
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting Alkoxysilane Assembly on Silica Surfaces: Grafting versus Homo-Condensation in Solution

Abstract: Silica surface functionalization is often done through the condensation of functional silanes on silanols, silica surfaces’ terminal groups. APTES, aminopropyltriethoxysilane, is widely used due to its assumed high reactivity with silanols, kinetically promoted by the catalytic action of the terminal amine function. Here, we revisit, based on a quantitative analysis by solid-state 29Si NMR, the assembly of this silane on silica surfaces to investigate whether its presence results from grafting, i.e., hetero-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…The coupling of dodecyltrichlorosilane onto SiO 2 nanoparticles via ball milling is shown in Figure b. The dodecyltrichlorosilane likely reacts with residual water molecules in the system via hydrolysis to form alkylsilane with OH end-groups and release of HCl, followed by a condensation reaction with surface silanol groups (Si–OH) of the intrinsically hydrophilic SiO 2 nanoparticles. A key advantage of the mechanochemical process with respect to the conventional wet-chemical processes (Figure c) is that the preparation time is dramatically reduced. The grafting is achieved within 5 min via ball milling, while in typical solvent-based conditions, grafting takes hours (Figure c). ,, Several factors may contribute to the fast grafting observed under ball milling conditions.…”
Section: Resultsmentioning
confidence: 99%
“…The coupling of dodecyltrichlorosilane onto SiO 2 nanoparticles via ball milling is shown in Figure b. The dodecyltrichlorosilane likely reacts with residual water molecules in the system via hydrolysis to form alkylsilane with OH end-groups and release of HCl, followed by a condensation reaction with surface silanol groups (Si–OH) of the intrinsically hydrophilic SiO 2 nanoparticles. A key advantage of the mechanochemical process with respect to the conventional wet-chemical processes (Figure c) is that the preparation time is dramatically reduced. The grafting is achieved within 5 min via ball milling, while in typical solvent-based conditions, grafting takes hours (Figure c). ,, Several factors may contribute to the fast grafting observed under ball milling conditions.…”
Section: Resultsmentioning
confidence: 99%
“…It is shown that water not only acts as a catalyst for the condensation reaction on the surface hydroxy groups, but it also enables polymerization. 35 While the polymerization reaction can increase amine loading if it occurs in the context of a multilayer reaction, excessive polymerization may lead to pore blockage and thereby decrease the accessibility of the amine adsorption sites. 31 Furthermore, excessive amounts of water in the solvent may lead to polymerization outside the support material, decreasing the grafting efficiency.…”
Section: ■ Introductionmentioning
confidence: 99%
“…These materials generally offer high CO 2 capacities, but the thick amine layer leads to high mass transfer resistances. ,, Grafting involves covalently bonding amine functionalities to the support material surface by silylation with the surface hydroxy groups, typically using a molecule with methoxy or ethoxy silane groups . Typically, the wet grafting procedure is used, in which a controlled amount of water is added to the support material before grafting. , Compared to dry grafting, higher amine loadings and therefore higher CO 2 uptakes can be achieved. An overview of the functionalization mechanisms is shown in Figure . It is shown that water not only acts as a catalyst for the condensation reaction on the surface hydroxy groups, but it also enables polymerization .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the combination of numerous carboxylate linkers and unprecedented SBUs of the general composition (RSiO 2 ) x M y would further enrich and deepen the understanding of MOF structures and properties. Finally, siloxanes are often considered as structural models for various building units of silicate minerals including zeolites, for example, polyhedral oligomeric silsesquioxanes mimicking the geometry of double n-rings found in various aluminosilicates. Therefore, synthetic efforts toward geometrically diverse metal–siloxane SBUs may ultimately lead to hybrid materials in which building units of MOFs and zeolites are joined at the molecular level and not as a bulk composite. , …”
Section: Introductionmentioning
confidence: 99%